BUSINESS PROPOSAL PREPARATION AND FINANCIAL REPORT ANALYSIS OF MSME ACTORS TO USE GROWING COMMUNITY INCOME IN SUBDISTRICT DAU, MALANG RAYA - Hernanik, Nova Dwi; Doloksaribu, Tio Ariella (International Journal of Multidisciplinary Research and Literature, 2024)
In Indonesia, micro, small, and medium-sized enterprises (MSMEs) play a significant role. MSMEs have demonstrated their resistance to internal crises and their perseverance. Additionally, a pandemic occurs. MSMEs are anticipated to recover from COVID-19, particularly among the District Dau Regency's MSME performers who are underprivileged in fields that include crafts, farming, fishing, and cooking. The group was selected due to the highest number of MSMEs in the Dau Malang Regency. And the region's plentiful natural resource, Power Natural (HR), is a potency source. The purpose of this study is to investigate and evaluate the efficacy of effort accompaniment in the creation and analysis of business proposals. Report Finance MSME Actors in the District of Dau so that they might serve as models and transform his company into a financially strong individual who can commit significantly to national finance. The study field (field research) method was applied, and one MSME actor and the head village (or that known program village) in each of the five chosen villages were directly interviewed